The Representation of Creditors’ Interests in Appointing a Bankruptcy Administrator - Dzindzelėtaitė-Šaltė, Lina (Teisė, 2019)
This article analyzes the representation of creditors’ interests in appointing a bankruptcy administrator and issues related to it. First of all, the aims of bankruptcy and various competing interests in the bankruptcy proceedings are evaluated. Further in the article the role of a bankruptcy administrator, the significance of the principle of creditor autonomy, and the right of creditors to participate in selecting and appointing a bankruptcy administrator are discussed. Theoretical and practical issues of selecting and appointing a bankruptcy administrator are identified as well.